Optimization of production and partial characterization of xylanase from a newly isolated Bacillus amyloliquefaciens - Chaves, Bruno Las-Casas (2022)
This paper reports the process of production optimization and partial characterization of xylanase from a newly isolated Bacillus amyloliquefacies VR002, isolated from local soil. The microorganism exhibited maximum xylanase production when 1.0% (v/v) of inoculum size was added to culture medium with initial pH 6, 1.0% (w/v) birchwood xylan, at 35 °C after 48h of incubation. Xylanase production in different carbon sources apart from birchwood xylan and xylose did not show high production levels. Optimum pH for xylanase activity was 6.0. The enzyme was alkali-stable and retained 100% of residual activity over the pH range from 6.0 to 10.0 for 24 h at 25°C. Optimum temperature for enzyme activity was 55°C. Xylanase was 100% stable at 4°C and 25°C even after 24h of incubation, a desirable characteristic for enzyme storage. Moreover, best crude extract volume and time reaction were found to be 10 µL and 5 min, respectively. After optimization of production and activity parameters, an increase of nearly 60-fold in xylanase activity (44.12 ± 4.36 U/mL) was achieved. Characteristics of B. amyloliquefaciens VR002 xylanase are particularly desirable for biotechnological applications